2016
DOI: 10.1038/ncomms12621
|View full text |Cite|
|
Sign up to set email alerts
|

Sequences flanking the core-binding site modulate glucocorticoid receptor structure and activity

Abstract: The glucocorticoid receptor (GR) binds as a homodimer to genomic response elements, which have particular sequence and shape characteristics. Here we show that the nucleotides directly flanking the core-binding site, differ depending on the strength of GR-dependent activation of nearby genes. Our study indicates that these flanking nucleotides change the three-dimensional structure of the DNA-binding site, the DNA-binding domain of GR and the quaternary structure of the dimeric complex. Functional studies in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 57 publications
(103 reference statements)
4
60
1
2
Order By: Relevance
“…Sequence divergence in the wing regions contributes to differences in DNA binding 1415 . The wing regions carry basic amino acids, which potentially recognize DNA structural features in the flanking regions of FOX binding sites, as previously observed for other transcription factor families 1618 . For forkhead proteins, a recent analysis of HT-SELEX data demonstrated that binding specificity predictions improve for models that augment nucleotide sequence with DNA shape features 19 .…”
Section: Introductionmentioning
confidence: 69%
“…Sequence divergence in the wing regions contributes to differences in DNA binding 1415 . The wing regions carry basic amino acids, which potentially recognize DNA structural features in the flanking regions of FOX binding sites, as previously observed for other transcription factor families 1618 . For forkhead proteins, a recent analysis of HT-SELEX data demonstrated that binding specificity predictions improve for models that augment nucleotide sequence with DNA shape features 19 .…”
Section: Introductionmentioning
confidence: 69%
“…2F). Finally, recent work has shown that sequences at the +8 and −8 positions flanking the GBS that alter DNA conformation also affect GR DBD structure, as assessed by NMR analysis in vitro and using a zinc-finger nuclease-generated, genomically integrated GBS-reporter system and endogenous GR in vivo 57 . Collectively, these studies suggest that DNA sequence-specific conformational states of GR result in the generation or stabilization of distinct patterns of GR surfaces, which serve as interaction platforms, driving alternative transcriptional outcomes.…”
Section: Allosteric Effectors Of Grmentioning
confidence: 99%
“…Natural and synthetic ligands, including FDA-approved drugs, bind to the NR LBD and affect NR activity through stabilizing specific LBD conformations that influence interactions with coregulators (Gronemeyer et al, 2004). NRs also bind DNA response elements of similar but varying sequences located in receptor target gene promoter regions via their DBD that also influence NR structure and activity (Meijsing et al, 2009; Schone et al, 2016; Watson et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…No large LBD structural changes have been observed in crystal structures of isolated NR LBDs compared to DNA-bound full-length receptor complexes (Chandra et al, 2008; Chandra et al, 2013; Helsen and Claessens, 2014; Lou et al, 2014). However, studies on glucocorticoid receptor (GR) have revealed that DNA can act as an allosteric nuclear receptor ligand, functioning in part by affecting the conformation of the DBD (Meijsing et al, 2009; Schone et al, 2016; Watson et al, 2013). Extending this concept beyond the DBD, hydrogen/deuterium exchange mass spectrometry (HDX-MS) studies on the vitamin D receptor (VDR)-RXRα heterodimer have shown that DNA binding can impact the conformation of surfaces remote from the DBD, including the receptor dimerization and AF-2 coregulator interaction surfaces located in the LBD (Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%